2017
DOI: 10.1080/09168451.2016.1189312
|View full text |Cite
|
Sign up to set email alerts
|

Using the CRISPR/Cas9 system to eliminate native plasmids of Zymomonas mobilis ZM4

Abstract: The CRISPR/Cas system can be used to simply and efficiently edit the genomes of various species, including animals, plants, and microbes. Zymomonas mobilis ZM4 is a highly efficient, ethanol-producing bacterium that contains five native plasmids. Here, we constructed the pSUZM2a-Cas9 plasmid and a single-guide RNA expression plasmid. The pSUZM2a-Cas9 plasmid was used to express the Cas9 gene cloned from Streptococcus pyogenes CICC 10464. The single-guide RNA expression plasmid pUC-T7sgRNA, with a T7 promoter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Finally, sophisticated and efficient tools for genome editing need to be developed instantaneously. For example, although CRISPR/Cas system has been investigated in Z. mobilis recently (Cao et al 2017a;Dong et al 2016), more efficient strategies are needed for efficient recreation of SNPs for genetics studies to identify the association of SNPs with improved phenotypes in tolerant mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, sophisticated and efficient tools for genome editing need to be developed instantaneously. For example, although CRISPR/Cas system has been investigated in Z. mobilis recently (Cao et al 2017a;Dong et al 2016), more efficient strategies are needed for efficient recreation of SNPs for genetics studies to identify the association of SNPs with improved phenotypes in tolerant mutants.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas systems can also target plasmid backbone genes such as replicase genes (Cao et al. 2017 ). CRISPR/Cas systems targeted and removed multiple AMR plasmids simultaneously (Yosef et al.…”
Section: Crispr/cas-based Plasmid Curing Systemsmentioning
confidence: 99%
“…Sequencing analysis revealed that all four plasmids encode replicases that are required for their replication. Thus, if these replicase genes were inactivated using the CRISPR-Cas12a-based toolkit, the plasmid would lose the ability for replication and will then be consequently cured [9,33].…”
Section: Application Of Crispr-cas12a System For Native Plasmid Curinmentioning
confidence: 99%
“…Plasmids play pivotal role in the advancement of molecular biology, and various plasmid vectors for genetic and metabolic engineering purposes have been developed using an origin of replication region from native plasmids of Z. mobilis [42]. Eight Z. mobilis strains have been completely sequenced and contain 2-8 native plasmids with different sizes [9,33]. Plasmid stability and compatibility issues will occur when an engineered plasmid with the same origin of replication is introduced into the host strain, which will limit the application of this powerful tool for strain improvement [43].…”
Section: Application Of Crispr-cas12a System For Native Plasmid Curinmentioning
confidence: 99%
See 1 more Smart Citation